Androgen Secreting Adrenal Adenoma – A Case report - Begum, Suraiya; Sharmin, Farzana; Biswas, Dhiraj Chandra; Jahan, Ismat Ara; Hossain, Munira (Northern International Medical College Journal, 2018)
Abstract not available Northern International Medical College Journal Vol.10(1) Jul 2018: 355-356